2015
DOI: 10.5539/jas.v7n12p165
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Social Capital in Rural Household Food Security: The Case Study of Dowa and Lilongwe Districts in Central Malawi

Abstract: This paper explores the contribution of social capital on the rural household food security. Social capital is the ability of community actors to secure benefits by virtue of membership in social networks or other structures. In the past decade, consensus has emerged among scholars and practitioners of development that social capital can contribute significantly to the alleviation of poverty. Food insecurity is an indicator of poverty. This paper therefore takes this view by investigating the impact of social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
1
13
0
3
Order By: Relevance
“…Older household heads have more experience that can be used for both increase in income and efficient spending of income and both can lead to food security. Dzanja et al (2015) also reported that, in Malawi, household head's age and food security status of household were significantly associated with each other at p<0.05. Number of earning members in a household was found positively significant for food security of households from Central Punjab.…”
Section: Discussionmentioning
confidence: 90%
“…Older household heads have more experience that can be used for both increase in income and efficient spending of income and both can lead to food security. Dzanja et al (2015) also reported that, in Malawi, household head's age and food security status of household were significantly associated with each other at p<0.05. Number of earning members in a household was found positively significant for food security of households from Central Punjab.…”
Section: Discussionmentioning
confidence: 90%
“…equal opportunities of access), effective participation, and a sense of recognition (including respecting and tolerating differences) [23]. Social cohesion is important because it can give rise to adaptive capacity and agency [19,24], such as enabling families to overcome periods of food shortage or illness [25]. While it is the combinations of assets that ultimately give rise to overall resilience [14], it is not always apparent which combinations will be most important.…”
Section: Enhance Adaptability and Flexibility Through Working With DImentioning
confidence: 99%
“…at the individual and household levels [56]. Similarly, evidence sought that social capital has a positive impact on achieving food security [57]. It is hypothesized that social capital has a positive association to household food security.…”
Section: Assessment Of Household Food Security In the Face Of Climatementioning
confidence: 99%